DIGITAL TECHNOLOGY AND MENTAL HEALTH: UNVEILING THE PSYCHOLOGICAL IMPACT OF MODERN DIGITAL HABITS - Spytska, Liana (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The rapid proliferation of digital technologies has significantly transformed modern life, raising concerns about their impact on mental health. This study aimed to identify the effects of digital technologies on the mental health of Ukrainians, focusing on cognitive functions, anxiety, depressive symptoms, physical activity. The study included surveys to identify the level of depressive symptoms, and personal and reactive anxiety that can result from excessive digital device use, alongside experiments to assess the impact of information overload and cyberbullying on mental health. Prolonged continuous use of digital devices negatively affected cognitive functions, including memory, attention, reaction time. Active digital device use before bedtime disrupted sleep phases. Excessive use also significantly reduced physical activity, particularly among older age groups, leading to prolonged sedentary behaviour. Young people showed better communication quality and group task performance in virtual interactions compared to older respondents. Personal anxiety levels remained stable across all age groups, despite information overload and cyberbullying. However, the highest levels of depressive symptoms were observed among middle-aged respondents, with younger and older groups displaying milder symptoms. The findings demonstrate the multifaceted negative effects of excessive digital technology use on mental health, including cognitive decline, disrupted sleep, reduced physical activity. Novel insights include stable anxiety levels irrespective of external stressors and varying depressive symptoms across age groups. These results highlight the urgent need for interventions to promote balanced digital technology use and tailored mental health strategies, particularly for middle-aged populations and older adults prone to sedentary behaviour.